Da’i Cadre Development Strategies at Al Fattah Islamic Boarding School: Strategi Pengembangan Kader Dakwah di Sekolah Asrama Islam Al Fattah - Helmi Faiz Amanulloh; Dzulfikar Akbar Romadlon (Universitas Muhammadiyah Sidoarjo, 2025)
General Background Islamic boarding schools play a central role in preparing religious cadres who can sustain Islamic preaching amid social and technological change. Specific Background The Al Fattah Islamic Boarding School in Sidoarjo applies structured programs combining traditional pesantren learning with contemporary approaches to respond to modern societal demands for competent da’i. Knowledge Gap Despite the strategic position of pesantren, systematic descriptions of integrated cadre development strategies aligned with contemporary da’wah challenges remain limited. Aims This study aims to describe the strategies of da’i cadre development implemented at Al Fattah Islamic Boarding School. Results Using a descriptive qualitative approach through interviews, observation, and documentation, the study identifies that cadre development is conducted through integration of formal and non-formal curricula, mastery of religious texts, moral and character formation, rhetorical training through muhadhoroh and munadhoroh, field da’wah practice, and the use of digital media. Traditional methods such as bandongan and sorogan are combined with soft-skill training, leadership preparation, alumni involvement, and continuous evaluation. Novelty The study highlights a comprehensive and systematic model that unites pesantren traditions with digital da’wah competencies within a single cadre development framework. Implications These findings provide a contextual reference for Islamic educational institutions in designing sustainable da’i cadre development models that remain relevant to contemporary social, cultural, and technological contexts. Highlights: Integration of Classical Learning Methods With Structured Non-Formal Training Forms a Coherent Preparation Model. Moral Cultivation and Exemplary Guidance Are Positioned as Foundational Components of Religious Leadership Preparation. Field Practice and Digital Media Utilization Expand Preaching Readiness in Diverse Social Contexts. Keywords: Da’I Cadre Development, Islamic Boarding School, Pesantren Curriculum, Digital Da’Wah, Moral Formation